Seychelles : First Review under the Extended Fund Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Seychelles. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
The expected macroeconomic recovery has materialized. Seychelles remains a leader in vaccine coverage at home, and the widespread availability of vaccines in Seychelles' key tourist markets, particularly Europe, is contributing to a strong rebound in tourism. The economic outlook, while positive, remains subject to the uncertain evolution of the COVID-19 pandemic globally.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Kosovo, Republic of